A New Captorhinid From the Permian Cave System Near Richards Spur, Oklahoma, and the Taxic Diversity of Captorhinus at This Locality - deBraga, Michael; Bevitt, Joseph J.; Reisz, Robert R. (Frontiers in Earth Science, 2019)
The early Permian cave system in the Dolese Brothers Limestone Quarry near Richards Spur, Oklahoma represents a unique depositional environment that has been interpreted as preserving an upland biota. The quarry and the region around it represent Paleozoic cave systems that underwent periods of flooding not unlike present-day conditions that are commonly associated with monsoonal episodes. The Richards Spur locality is particularly rich in captorhinid eureptiles which represent one of the earliest reptilian clades to have evolved a specialized dentition. Although the multiple-tooth rowed Captorhinus aguti is the most abundant captorhinid at Richards Spur, at least one other species has been described (Captorhinus magnus) and assigned to the same genus, but five other captorhinid taxa have also been found. We describe a new member of the genus Captorhinus (Captorhinus kieranensis) and explore details of the dental anatomy against the two other members of the genus at Richards Spur, C. aguti and C. magnus, as well as with a member of the genus not presently known from Richards Spur (C. laticeps). Findings suggest that the nature of the ogival dentition described previously as a synapomorphy uniting C. aguti with C. magnus is not supported and we propose a more informative method for differentiating among dental characters within the clade. The discovery of a new species of Captorhinus provides additional evidence for captorhinid taxic diversity at Richards Spur and is supportive of niche partitioning, which is likely associated with reducing intra-specific competition within the clade. Finally, we argue that the captorhinid fossils at Richards Spur likely includes one additional, currently undescribed multiple-tooth rowed form, that renders the current practice of assigning disarticulated cranial remains, specifically dental fragments, to the species C. aguti problematic.